1979
DOI: 10.1042/cs0560501
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phenobarbitone on Plasma Apolipoprotein B and Plasma High-Density-Lipoprotein Cholesterol in Normal Subjects

Abstract: 1. Further observations from an earlier study in which phenobarbitone in a dose of 180 mg daily was administered to ten normal men and women for 3 weeks are reported. There was a significant increase in plasma high-density-lipoprotein (HDL) cholesterol concentration and in the concentration of both total plasma and low-density-lipoprotein (LDL) apolipoprotein B. 2. There was no change in the ratios of the cholesterol:apolipoprotein B and triglyceride:apolipoprotein B in LDL. 3. There was no significant change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…The observed increase in HDL-c in patients treated with both nevirapine and EFV has been shown to be accompanied by an increase in levels of apo A1 in plasma. 11,27 Favorable dose-dependent increases in levels of HDL-c [28][29][30] and apo A1 31 have also been observed in patients receiving antiepileptic agents. One study suggests that the observed increase in apo A1 mRNA expression in cell lines exposed to phenobarbital is a result of an increase in apo A1 transcription.…”
Section: Discussionmentioning
confidence: 99%
“…The observed increase in HDL-c in patients treated with both nevirapine and EFV has been shown to be accompanied by an increase in levels of apo A1 in plasma. 11,27 Favorable dose-dependent increases in levels of HDL-c [28][29][30] and apo A1 31 have also been observed in patients receiving antiepileptic agents. One study suggests that the observed increase in apo A1 mRNA expression in cell lines exposed to phenobarbital is a result of an increase in apo A1 transcription.…”
Section: Discussionmentioning
confidence: 99%
“…14,16 Equally, our results do not support the HDL-C = high-density lipoprotein cholesterol; LDL-C = low-density lipoprotein cholesterol; VLDL-C = very-low-density lipoprotein cholesterol. 5,7,13,15,18 Reports on the effects of valproic acid on lipid measurements are conflicting. Statistically significant difference with respect to corresponding treatment mean (normal diet): ***P < .05.…”
Section: Discussionmentioning
confidence: 99%
“…This may significantly alter drug disposition and serum concentration of sex hormones. In addition, the concentration of plasma HDL-cholesterol and apolipoprotein B rise during treatment with phenobarbitone (Durrington, 1979) or phenytoin (Nikkila et al, 1978). However, these effects are not seen when phenobarbitone is given in low dosage (Perucca et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the effect of phenobarbitone and phenytoin in raising HDL-cholesterol (Durrington, 1979;Nikkila et al, 1978) is also due to enzyme induction. In patients receiving these enzyme inducers plasma HDL concentrations are proportional to the magnitude of the induction assessed directly by liver cytochrome P-450 content and indirectly by plasma antipyrine clearance rate (Luoma et al, 1982).…”
Section: Introductionmentioning
confidence: 99%